2020
DOI: 10.1111/jpm.12687
|View full text |Cite
|
Sign up to set email alerts
|

Perceived quality of primary healthcare services and its association with institutional trust among caregivers of persons diagnosed with a severe mental illness in China

Abstract: Accessible summary What is known on the subject Low utilization of the family‐oriented community rehabilitation services is a threatening challenge facing low‐ and middle‐ income countries. Family caregiver’s trust in community healthcare providers is the precondition of service utilization and is shaped by their perceived quality of primary healthcare services from previous experience. Most of the studies concerning the relationship between perceived quality and institutional trust were conducted in western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 61 publications
(101 reference statements)
0
3
0
Order By: Relevance
“…Distrust in medical institutions and perceived stigma toward psychiatric treatment are prevalent ( Qi et al, 2021 ; Thornicroft et al, 2022 ), making patients with skin diseases even more reluctant to seek psychological help. Our findings indicated that a large number of patients believed that mental health care might not be effective on skin diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Distrust in medical institutions and perceived stigma toward psychiatric treatment are prevalent ( Qi et al, 2021 ; Thornicroft et al, 2022 ), making patients with skin diseases even more reluctant to seek psychological help. Our findings indicated that a large number of patients believed that mental health care might not be effective on skin diseases.…”
Section: Discussionmentioning
confidence: 99%
“…There are, however, relatively few studies that emphasize the possible negative consequences for having no or highly limited contact with relatives (between family and health professionals and family and patient). For example, Qi et al ( 32 ) shed light on vulnerable families concerned about the need for confidentiality, but their worry was connected to the feeling of stigma rather than to stakeholders within the family having different views and needs in relation to confidentiality. In this case, the patient's best interest seems to be compatible with the concerns of the whole family.…”
Section: Discussionmentioning
confidence: 99%
“…The scientific literature also identifies the existence of institutional trust, seen as the trust of citizens in public bodies [12], which has been addressed in recent research due to its impact on business management, in economic order and sustainability [59][60][61][62][63][64][65][66][67][68][69][70][71][72][73]. It is precisely on this trust that our study is based, since we will specifically analyze trust in large companies and in banks.…”
Section: Different Types Of Trust and Institutional Trustmentioning
confidence: 99%